Implementation of Talent Management in the Healthcare Sector (Hospital) - Sativa, Orieza; Rinawati, Rinawati (International Journal Administration, Business & Organization, 2025)
This research discusses the application of talent management strategies in the health sector, especially hospitals, in order to improve organizational performance and service quality. Using a qualitative approach through a literature review, this research examines various national and international sources. The results showed that talent management plays an important role in improving employee engagement, clinical competence, and service efficiency. Key components of this strategy include competency-based recruitment, structured career development, and strategic retention mechanisms. However, challenges remain, such as unobjective selection systems and a lack of incentives for top talent. This research recommends the implementation of data-driven systems, standard operating procedures, and the cultivation of a fair and merit-based work culture. Overall, integrated talent management can support the sustainable development of Human Resources and strengthen the hospital's competitiveness in the face of global challenges and technological advancements.